Legal aspects of functional security standardisation of the Internet of Things - P. S. Klimushyn; V. Ye. Roh; T. P. Kolisnyk (Law and Safety)
IoT technologies provide smart things with the ability to make decisions in the management of physical objects using intelligence and consensus. To support the Internet of Things, technologies such as built-in devices, cloud and fog computing, big data processing, machine learning, and artificial intelligence are used to produce intelligent physical objects. A review of existing security infrastructures for IoT-based intelligent environments shows that every connected device can be a potential entry point for an attack.